1999
DOI: 10.1152/jappl.1999.87.6.2115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hindlimb unloading on rat cerebral, splenic, and mesenteric resistance artery morphology

Abstract: Hindlimb unloading (HU) of rats induces a cephalic shift in body fluids. We hypothesized that the putative increase in cranial fluid pressure and decrease in peripheral fluid pressure would alter the morphology of resistance arteries from 2-wk HU male Sprague-Dawley rats. To test this hypothesis, the cerebral basilar, mesenteric, and splenic arteries were removed from control (C) and HU animals. The vessels were cannulated, and luminal pressure was set to 60 cmH(2)O. The resistance arteries were then relaxed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
104
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 33 publications
14
104
0
Order By: Relevance
“…Reduced cerebrovascular dynamic autoregulation after long-duration spaceflight was consistent with some (38) but not all (29) findings after HDBR and with astronauts who had orthostatic intolerance after short-duration spaceflights (8). Altered postflight cerebrovascular control might reflect the structural and functional changes observed in the animal models of spaceflight (24,34,36,37).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Reduced cerebrovascular dynamic autoregulation after long-duration spaceflight was consistent with some (38) but not all (29) findings after HDBR and with astronauts who had orthostatic intolerance after short-duration spaceflights (8). Altered postflight cerebrovascular control might reflect the structural and functional changes observed in the animal models of spaceflight (24,34,36,37).…”
Section: Discussionsupporting
confidence: 63%
“…The human HDBR studies reported variable results with increases, decreases, and no change in CBFV. Animal models have revealed reduced flow (34,35) accompanied by significant structural changes with increased thickness of vessel walls (24,34,36,37) and reduced internal dimensions (36). The animal models also suggested an involvement of renin-angiotensin system might in structural modifications with hind limb suspension (6,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of medial layer of basilar arteries was increased by HDT (Table 3), which is consistent with the finding in rat basilar artery [10]. Our results suggest that the vascular reactivity to KCl and 5-HT, but not to NE, was enhanced by exposure to HDT in proportion to the medial hypertrophy.…”
Section: Discussionsupporting
confidence: 91%
“…The animals were randomly assigned to either cage control (n ϭ 43) or 14 day HU (n ϭ 44) groups. The hindlimbs of the HU group were elevated to an approximate spinal angle of 40 -45°via orthopedic tape adhered to the tail (5,15,56), which is a modification of techniques previously described (58). Control animals were individually housed and maintained in a normal cage environment, while HU rats were kept in the head-down position for 14 days.…”
Section: Animalsmentioning
confidence: 99%